The Consumption of Capital in Austria - Machlup, Fritz (The Review of Economics and Statistics, 1935)
THE Austrian theory of economics has often been reproached with over-abstractness and remoteness from real life. The Austrian theory of consumption of capital is, unfortunately, more than an unreal construction based upon unreal assumptions, more than a plaything for the mental gymnastics of scholars; it is an attempt to explain very real facts. The discussion of capital consumption and economic decline was provoked by the course of events observed in Austria during the war, during the post-war inflation, and during the years of social reform.2 Physical destruction and value destruction of capital. What is the connection between physical destruction and value destruction of capital? The two things do not always run parallel. When capital equipment is physically destroyed say by war, by fire, by wear and tear its value is gone simultaneously. But the, loss in value might occur before the capital goods are physically impaired. Equipment might be rendered valueless by certain economic changes. It is then, so to speak, designated for progressive dilapidation; it does not pay to maintain equipment of no value; hence the physical destruction will follow the value destruction after a considerable lag. There is a case in which the capital values in terms of money decrease without any physical capital destruction following: that of the fall in costs of reproduction. For some purposes the statistician who records values of capital will find it adequate to correct the figures for changes in costs of reproduction. Sources of information about changes in capital stock. In a growing economy, factual information about capital formation is obtained in three ways: (i) by figures concerning new physical equipment, especially activity in the construction industries, (2) by figures concerning the supply of money capital from the various sources, and (3) by figures concerning the valuation of the existing capital of corporations. For a declining economy only the third way seems practicable. The difference between the valuation of capital at different points of time is the measure for the decline. The reasons for such a decline are to be sought either in physical destruction of capital, or in depreciation by changes in the horizontal economic structure such as changes in demand, or in the consumption of capital. The Austrian Institut fur Konjunkturforschung (Institute for Business Cycle Research) undertook such a comparison of the valuation of stocks over a period of i8 years. A report was published by Dr. Oskar Morgenstern in the Zeitschrift fi4r National5konomie. Some of the results are shown on Table I (page I5). The valuation arrived at for corporation capital in Austria in I9I3 is compared in the table with the valuation in I930. Both sums were obtained by combining the capital values of all Austrian corporations the shares of which were listed on the Viennese stock exchange. The value of capital of each corporation was calculated by multiplying the number of shares issued by the average price during the whole year. Corporations which existed in I9I3 but had disappeared in I930 were not included in either sum. Only the surviving firms or merged firms were taken into account. This procedure concealed the loss of capital of corporations which disappeared completely, but it was imposed by the fact that some corporations had moved, following the dismemberment of the Austrian monarchy, from Vienna into the capitals of the new nations. The investigation was therefore confined to all Austrian corporations which existed in io9o. Those which had been founded later 1 This article is based upon an address delivered at a meeting of the Boston Chapter of the American Statistical Association on December 3, I934. 2 Literature: Professor Ludwig v. Mises was the first, so far as I know, to point to the phenomenon of the consumption of capital. As a member of a committee appointed by the Austrian Government (including two other committeemen, Dr. Dollfuss and Dr. Palla) he also emphasized comprehensive factual information. See Bericht uiber die Ursachen der wirtschaftliclsen Schiwierigheiten in Oesterreich (Vienna, I93I). An important investigation of the capital of Austrian corporations was made by the Institut fur Konjunkturforschung. See Oskar Morgenstern, Kapitalund Kurswertanderungen der an der Wiener B6rse notierten 6sterreichischen Aktiengesellschaften I9I3 bis I930, Zeitschrift far Nationalikonomie, iII (I932). For theoretical expositions see F. A. v. Hayek, Kapitalaufzehrung, Weltwirtschaftliches Archiv, xxxvi (I932), and Erich Schiff, Kapitalbildung und Kapitalaufzelrung im Konjunkturverlauf (Vienna, I933). For a short survey on the Austrian experience see Nicholas Kaldor, The Economic Situation of Austria, Harvard Business Review, xi (I932).